2018
DOI: 10.12998/wjcc.v6.i14.854
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional and topical glucocorticoids for pretibial myxedema: A case report and review of literature

Abstract: Pretibial myxedema (PTM), an uncommon manifestation of Graves’ disease (GD), is a local autoimmune reaction in the cutaneous tissue. The treatment of PTM is a clinical challenge. We herein report on a patient with PTM who achieved complete remission by multipoint subcutaneous injections of a long-acting glucocorticoid and topical glucocorticoid ointment application for a self-controlled study. A 53-year-old male presented with a history of GD for 3.5 years and a history of PTM for 1.5 years. Physical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Intralesional and topical corticosteroids are considered first-line therapy for PTM, although topical application appears to be significantly less effective. 1 , 8 , 9 Zhang et al 8 reported nearly 100% complete response rates to weekly injections of intralesional triamcinolone 10 mg/mL for all variants with the exception of elephantiasis, which had a partial response in 73% of patients. In a case series of 178 patients with PTM, only 20.8% of the 96 patients treated with topical corticosteroids achieved complete remission over an average of 8.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional and topical corticosteroids are considered first-line therapy for PTM, although topical application appears to be significantly less effective. 1 , 8 , 9 Zhang et al 8 reported nearly 100% complete response rates to weekly injections of intralesional triamcinolone 10 mg/mL for all variants with the exception of elephantiasis, which had a partial response in 73% of patients. In a case series of 178 patients with PTM, only 20.8% of the 96 patients treated with topical corticosteroids achieved complete remission over an average of 8.8 years.…”
Section: Discussionmentioning
confidence: 99%